2016
DOI: 10.1038/srep39780
|View full text |Cite|
|
Sign up to set email alerts
|

ADAM17/EGFR axis promotes transglutaminase-dependent skin barrier formation through phospholipase C γ1 and protein kinase C pathways

Abstract: The vitally important skin barrier is formed by extensive cross-linking activity of transglutaminases (TGs) during terminal epidermal differentiation. We have previously shown that epidermal deficiency of a disintegrin and metalloproteinase 17 (ADAM17), the principal EGFR ligand sheddase, results in postnatal skin barrier defects in mice due to impeded TG activity. However, the mechanism by which ADAM17/EGFR signalling maintains TG activity during epidermal differentiation remains elusive. Here we demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 55 publications
(101 reference statements)
1
20
0
Order By: Relevance
“…Thus, TG1 and TG3 are indispensable enzymes for CE formation, which eventually determine the properties of the skin epidermis under several cellular signaling and regulation . Knockdown of either TG1 or TG3 in the 3D cultured cells, as expected, resulted in aberrant formation of the cornified layer as they matured to the differentiated stage in keratinocytes.…”
Section: Discussionsupporting
confidence: 56%
“…Thus, TG1 and TG3 are indispensable enzymes for CE formation, which eventually determine the properties of the skin epidermis under several cellular signaling and regulation . Knockdown of either TG1 or TG3 in the 3D cultured cells, as expected, resulted in aberrant formation of the cornified layer as they matured to the differentiated stage in keratinocytes.…”
Section: Discussionsupporting
confidence: 56%
“…FABP2 and TGM2 have both been implicated in the development and progression of IBD . In addition, ADAM17/EGFR signaling mechanisms have been shown to regulate TGM2 activity during epithelial cell differentiation . Transcriptional levels of FABP2 and TGM2 in Il10 −/− / Rhbdf2 −/− mice were found to be similar to that of Rhbdf2 −/− or Il10 −/− mice and WT controls, indicating that RHBDF2 may not be responsible for the regulation of FABP2 and TGM2 at the genetic level under chronic inflammation (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…PLCγ1 cKO mice showed normal expression of differentiation markers, namely keratin 5, keratin 1, filaggrin and loricrin (Figure B and C). Since a previous in vitro study has suggested that PLCγ1 plays a critical role in the induction of transglutaminase activity in primary keratinocytes, we examined transglutaminase activity in interfollicular epidermis. However, enzymatic activity of transglutaminase was not found to be altered in interfollicular epidermis of PLCγ1 cKO mice (Figure B).…”
Section: Resultsmentioning
confidence: 99%